Ecocriticism and Shakespeare - Estok, Simon C. author. aut Link
X, 182 p. 4 illus.
Keywords: This book offers the term 'ecophobia' as a way of understanding and organizing representations of contempt for the natural world. Estok argues that this vocabulary is both necessary to the developing area of ecocritical studies and for our understandings of the representations of 'Nature' in Shakespeare.